Performance measurement and KPIs for remanufacturing - Ian Graham; Paul Goodall; Yi Peng; Claire Palmer; Andrew West; Paul Conway; Julien Etienne Mascolo; Fritz Ulrich Dettmer (Journal of Remanufacturing, 2015)
The paper provides a brief background to remanufacturing and the general use of Performance Measurement and Key Performance Indicators (KPIs) before introducing selected and newly formulated KPIs designed specifically for remanufacturing. Their relationships with the remanufacturing challenges faced by two contrasting remanufacturing businesses and the wider reman industry are described in detail. Subsets of KPIs forming a 'Balanced Scorecard' for each of the two remanufacturing cases conclude the paper. They arise through close working with Centro Ricerche FIAT (CRF) and SKF, and are triangulated by literature review and wider expert interviews. The two businesses represent contrasting remanufacturing scenarios: well-established high-volume low-margin automotive engine remanufacturing by the OEM ( >1000 units per year, < exteuro10 k per unit) verses low-volume high-value wind turbine gearbox reman by an independent start-up ( < 100 units per year, > exteuro100 k per unit). The 10 general production engineering KPIs selected for the reman KPI toolbox are as follows: Work In Progress (WIP), Overall Equipment Effectiveness (OEE), Lead Time (LT), Cycle Time (CT), Hours Per Unit (HPU), Product Margin (PM), Quotation Accuracy (QA), Number of Concessions (NC), Number of managed mBOMs (BOM), and Personnel Saturation (PS). The Eco KPIs selected are: Material Used (MU), Recycled Material Used (RMU), Direct Energy Consumption (ECD), Indirect Energy Consumption (ECI), Water Withdrawal (WW), Green House Gas emissions (GHG), Total Waste (TW) by weight. The 8 Remanufacturing KPIs compiled and formulated as part of this research are: Core / Product Ratio (CPR), Core / Product Value Ratio (CPV), New Component Costs (NCC), Component Salvage Rate (SRC), Product Salvage Rate (SRP), Core Disposal Rate (CDR), Core Class Accuracy (CCA), and Core Class Distribution (CCD).
Keywords: 650; Remanufacturing; KPI; Key performance indicator; Performance measurement